2019
DOI: 10.21037/atm.2019.06.17
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide reduces cardiomyocyte apoptosis by stimulating adiponectin secretion and activating APPL1-AMPK-PPARα axis

Abstract: Background: To explore the mechanism that exenatide reduces cardiomyocyte apoptosis via the adiponectin pathway in vitro.Methods: Cardiomyocytes were randomly divided into the control group (group C), diabetic group (group D), diabetic + exenatide treatment group (group DE), diabetic + exenatide treatment + APPL1 overexpression group (group OE), and diabetic + exenatide treatment + APPL1 knock-down group (group KD). After 48 h culture, the apoptosis rate, the adiponectin level in the cell culture fluid, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…However, only p-AMPK levels were firmly enhanced after ON treatment. The benefits of p-AMPK stimulation have been previously observed in many cardiovascular diseases, including MI and ischemia reperfusion injury (36)(37)(38). In the present study, AMPK activation inhibited the phosphorylation of mTOR, leading to an increase in autophagy.…”
Section: Discussionsupporting
confidence: 64%
“…However, only p-AMPK levels were firmly enhanced after ON treatment. The benefits of p-AMPK stimulation have been previously observed in many cardiovascular diseases, including MI and ischemia reperfusion injury (36)(37)(38). In the present study, AMPK activation inhibited the phosphorylation of mTOR, leading to an increase in autophagy.…”
Section: Discussionsupporting
confidence: 64%
“…On the one hand, the breast density in premenopausal women is higher than that in postmenopausal women; therefore, the improvement in the difference may be more obvious. On the other hand, previous studies suggested that diabetic patients have lower levels of adiponectin than healthy people and that improvement in lifestyle can also improve the adiponectin levels, 51 which may contribute to reducing breast density.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of diabetic rats, the GLP1RA exenatide decreased cardiomyocyte apoptosis and improved cardiac function. This effect was associated with increased AMPK phosphorylation, activating its activity [ 106 ]. In addition, it has been reported that liraglutide ameliorates the lipotoxic, inflammatory effects of high-calorie diet feeding in vivo and palmitic acid treatment in vitro via inhibition of the mTORC1 signaling pathway [ 107 ].…”
Section: Glp1ra Effects On Cellular Agingmentioning
confidence: 99%